Effects of moisture content, wood species, and form of raw materials on fiber morphology and mechanical properties of wood fiber‐HDPE composites. Issue 9 (23rd May 2017) - Gao, Xun; Li, Qingde; Cheng, Wanli; Han, Guangping; Xuan, Lihui
Abstract : Use of high‐quality wood fibers as reinforcement materials in wood‐plastic composites (WPCs) significantly improves the overall performance of the resulting WPCs. This study focused on the preparation of various types of wood fibers for subsequent use in WPCs. Further, effects of moisture content, wood species, and form of raw material on the quality of prepared wood fibers and on the mechanical properties of wood fiber‐reinforced high‐density polyethylene were comprehensively investigated. The main findings indicated that the overall size of wood fibers increased significantly with the initial moisture content of raw materials; the best morphological features of fibers and the best corresponding mechanical properties of WPCs were obtained for an initial moisture content of 30 wt%. The lengths and diameters of wood fibers prepared from veneers were larger than those of fibers prepared from chips. A wood fiber diameter between 0.21 and 0.29 mm (60–80 mesh) and a length to diameter ratio between 5 and 8 yielded the best mechanical properties for the resultant products. Finally, the composites reinforced with pine fibers exhibited mechanical properties superior to those reinforced with poplar fibers. POLYM. COMPOS., 39:3236–3246, 2018. © 2017 Society of Plastics Engineers